A Two-Microphone Noise Reduction System for Cochlear Implant Users with Nearby Microphones—Part I: Signal Processing Algorithm Design and Development. (6th May 2008) - Kompis Kompis, Martin Martin; Bertram Bertram, Matthias Matthias; François François, Jacques Jacques; Pelizzone Pelizzone, Marco Marco
Abstract : Users of cochlear implant systems, that is, of auditory aids which stimulate the auditory nerve at the cochlea electrically, often complain about poor speech understanding in noisy environments. Despite the proven advantages of multimicrophone directional noise reduction systems for conventional hearing aids, only one major manufacturer has so far implemented such a system in a product, presumably because of the added power consumption and size. We present a physically small (intermicrophone distance 7 mm) and computationally inexpensive adaptive noise reduction system suitable for behind-the-ear cochlear implant speech processors. Supporting algorithms, which allow the adjustment of the opening angle and the maximum noise suppression, are proposed and evaluated. A portable real-time device for test in real acoustic environments is presented.